Portable interactive visualization of large-scale simulations in geotechnical engineering using Unity3D. (October 2020) - Wang, Rong-Xin; Wang, Rui; Fu, Pengcheng; Zhang, Jian-Min
Highlights: Lightweight visualization software for large-scale geotechnical engineering simulation. Visualization of models with time-varying attributes attached to fixed mesh and models with time-varying mesh. Effective data preprocessing massive-sized parallel simulation data. Efficient data access and rendering optimization for smooth user interactivity. Deployed on various operating platforms for portable devices. Abstract: Development in large-scale geotechnical engineering simulation places tremendous demand for efficient visualization of such simulation data. This study presents a lightweight software tool, i.e. Geotechnical Interactive Visualization (GIV), as a solution to this challenge, which achieves efficient interactive visualization of large-scale simulations data in geotechnical engineering. Visualization data flow and algorithms specifically optimized for common geotechnical engineering applications are implemented in GIV. GIV can visualize geotechnical structure models with time-varying attributes attached to mesh with fixed topology, and also models with time-varying mesh topologies but no attributes attached, the two most common visualization tasks in geotechnical engineering. Challenges for large-scale simulation data visualization, including parallel simulation data redundancy, massive data size, dynamic user interaction, and portability are overcome via specifically designed algorithms for simulation data preprocessing and optimized visualization modules using the powerful 3D rendering and interactive game engine Unity3D. Comparison of GIV with several widely used visualization tools for the visualization of large-scale idealized datasets and realistic geotechnical simulations highlights the visualization efficiency, smooth interactivity, and lightweight features of GIV.